Warrior mindset : the tao of a Champion - Gracie, Roger (St. Martin's Press, 2025)
"A guide to self-mastery and other lessons based on the principles of Brazilian Jiu Jitsu, by the sport's greatest practitioner of all time. As a ten-time Brazilian jiu jitsu World Champion and a former MMA World Champion, Roger Gracie is widely considered to be the greatest practitioner of Brazilian jiu jitsu of all time. His grandfather, the great Carlos Gracie, was the architect of modern day Brazilian jiu jitsu and for Roger, growing up in the famous Gracie family, every conversation seemed to be about fighting. Within this family of supermen, this self-contained, chubby kid promised little; in fact, nobody expected Roger to become the warrior he later did. But once he had made up his mind as a teenager to become the greatest, Roger's star was firmly aligned with his purpose. Over time, he gradually became unstoppable, both in his thirst for jiu jitsu knowledge and in his single-mindedness to strip back overly complex moves to their simplest most effective forms, just as his grandfather had done before him. In Warrior Mindset: The Tao of a Champion, for the first time, Gracie shares lessons from a career of fighting at the highest level including: - Learning to breathe - Controlling your emotion - Mastering your thinking - Developing quiet inner grace. Going far beyond the mat, this hard-won wisdom is applicable to everyone from any background and in any walk of life who longs to find strength, courage, health, and peace."--Jacket flap.